Избранное - Гоголь Николай Васильевич (Библиотека мировой литературы для детей, 2001)
Экземпляры: (20190701) / Инвентарный номер: 28423 / Цена: 50.20 / Сис.шифр: Р1 / Авт.знак: Г 58 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)1